PEMANFAATAN MOL NIRA AREN DALAM MENDUKUNG PERTANIAN BERKELANJUTAN MELALUI PROGRAM PENYULUHAN DI KECAMATAN RASANAE TIMUR, KOTA BIMA - Muniarty, Puji; Haryanti, Intisari; Rimawan, M; Ovriyadin, Ovriyadin; Wulandari, Wulandari (Universitas Mataram, 2024)
The agricultural potential in East Rasanae District is also supported by plantation potential, one of which is palm trees. Palm sap produced is still sold in logs, so the shelf life is very low, resulting in damage and the product is wasted, resulting in low economic value. Based on observation visits and interviews with the Chair of KWT Mekar Sari, it was found that problems included a lack of quantity of chemical fertilizer and a lack of knowledge and skills of women farmers in processing and utilizing palm sap natural resources. Beginner Community Empowerment Program (PMP) which involves farmers, especially women farmers who are members of KWT Mekar Sari with a total of 30 members with an organic plant cultivation business that uses the home yard as business land and agricultural extension officers with support academic community as the initiator of agricultural transformation in Bima City by utilizing the potential of sap processing so that it is not wasted. The main objective of implementing Beginner Community Service with KWT Mekar Sari Partners is to achieve one of the MBKM programs at IKU2, IKU3, IKU5 & as a vehicle for mentoring women farmers. Activities using cooperative methods targeting women-KWT Mekar Sari. The results of the activity provide the benefit of increasing the knowledge and skills of partner members in processing palm sap mole & carrying out simple bookkeeping records, increasing the ability and knowledge of partner members in managing MSME businesses so that they have a good management system, realizing organizational management functions that can carry out duties and responsibilities effectively. clearly focused on partner members and increasing partners' knowledge & abilities in packaging and digital marketing via FB, WA and IG so as to increase competitiveness and expand the market and increase partner turnover.